Reports on categorization and classification of human rights violations in Chile (1974–1978). (January 2019) - Ruiz, Marcela; Bernasconi, Oriana
This study analyzes socio-discursive categories used to define and classify the political violence exerted in Chilean human rights reports (1974–1978) to understand the emergence of the repertoire of repression and the construction of victimhood as a social recognition and communicative process in Latin America during the 1970s. These reports are addressed as a professional discursive genre produced by non-governmental organizations whose purpose is to denounce the violation of human rights in the context of political controversies as well as in the Chilean totalitarian context. The discursive genre is characterized by objectivity, the credibility of the information, the event-based approach, the use of statistics to establish the type and magnitude of the violation of human rights. The corpus analyzed consists of 44 reports belonging to human rights archives. The statistical section and comments were coded according to narrative categories (participants, action, cause, time and space). The results show the predominance of the legal perspective to classify the violation of human rights, the emergence of the category of enforced disappearance, the relationship with the socio-political context and the categories elaborated to identify patterns of violation of human rights.